2016
DOI: 10.1590/0104-6632.20160333s20150125
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation Combined With Equivalent Diameter for Turbulent Jet Modelling and Gas Dispersion

Abstract: CFD modelling combines transport phenomena and numerical approaches to solve physical problems. Although numerical modelling of flow scenarios is the cutting edge of flow modelling, there seems to be room for improvement. This paper proposes an approach for jet modelling in a low Mach number computational code. The methodology is based on the equivalent diameter and velocity profile calculated downstream from the jet leak orifice. The novel model DESQr (Diameter of Equivalent Simulation for Quicker Run) is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The hatched region in Fig. 2 around whereas low concentrations of Mn 2+ or [Fe(CN) 6 ] 3À (<0.5 M) are unfavorable for the formation of pattern E. It is also noteworthy that pattern E was generated locally in a highly stochastic manner, showing an interesting similarity to turbulent-ow leakage from pressure vessels 15 or liform corrosion. 16 Further comparative studies are needed to better understand this new self-organized pattern formed in precipitation reactions far from the equilibrium.…”
Section: Precipitation Patterns Of Mn-fe Pbas In Agarose Gelsmentioning
confidence: 89%
“…The hatched region in Fig. 2 around whereas low concentrations of Mn 2+ or [Fe(CN) 6 ] 3À (<0.5 M) are unfavorable for the formation of pattern E. It is also noteworthy that pattern E was generated locally in a highly stochastic manner, showing an interesting similarity to turbulent-ow leakage from pressure vessels 15 or liform corrosion. 16 Further comparative studies are needed to better understand this new self-organized pattern formed in precipitation reactions far from the equilibrium.…”
Section: Precipitation Patterns Of Mn-fe Pbas In Agarose Gelsmentioning
confidence: 89%
“…The over-prediction of FDS may be due to that a constant coefficient Smagorinsky model was adopted in the simulation. However, the dynamic Smagorinsky model was shown to improve the gas dispersion prediction (Ferreira Jr. and Vianna, 2016). This indicates that it would be a promising approach to use LES in order to enhance the performance of the developed solver.…”
Section: Ground Heat Transfer Sensitivity Studymentioning
confidence: 99%
“…Many scholars have undertaken efforts to improve the accuracy of numerical simulation. Ferreira et al [18] proposed a novel jet model, DESQr (Diameter of Equivalent Simulation for Quick Run), which was implemented in the framework of FDS (Fire Dynamics Simulator) and able to capture turbulent eddies in a simulation. Vianna et al [19] modified the classic porosity distributed resistance formulation, and suggested a new model that represented the part of the filtered geometry from the original model through the porosity values of the unstructured tetrahedral mesh.…”
Section: Introductionmentioning
confidence: 99%